Climate change policies reduce air pollution and increase physical activity: Benefits, costs, inequalities, and indoor exposures - Sean Beevers; Nosha Assareh; Andrew Beddows; Gregor Stewart; Mike Holland; Daniela Fecht; Yunzhe Liu; Anna Goodman; Heather Walton; Christian Brand; Dimitris Evangelopoulos; Dylan Wood; et al. (Environment International)
The burden of diseases attributable to air pollution is comparable to those of global health risks such as unhealthy diets and tobacco smoking, with many air pollution sources also emitting climate heating gases. In this UK study we estimated the co-benefits of Net Zero (NZ) climate policy on the health benefits of air pollution reduction, increased active travel, outdoor exposure inequalities and indoor air pollution changes. The study focused on two of the largest UK sources, road transport and building heating, with comparisons made between NZ and UK existing policy, referred to as Business as Usual (BAU). Particulate matter (PM2.5), Nitrogen Dioxide (NO2) and Ozone (O3) projections were made between 2019 and 2050, with emphasis placed upon the NZ co-benefits in 2030 and 2040. We compared the UK BAU scenarios with the Climate Change Committee’s (CCC) Balanced Net Zero Pathway (BNZP) and Widespread Innovation (WI) pathway.Compared to BAU predictions, BNZP assumptions lead to more electric vehicles, reduced vehicle km, more low carbon building heating, and reduced emissions of NO2 and PM2.5. By 2040 under BNZP, relative to BAU, the buildings sector was predicted to be three times more effective at reducing PM2.5 than road transport. To help reduce the inequality gap the NZ building transition was tailored toward those most in need. Outdoor air pollution exposure inequalities prevailed across the socioeconomic spectrum, especially for NO2, but were less pronounced due in part to NZ policies. Core air quality health benefits for the BNZP buildings sector were £21.3 billion (16.4 to 26.2) by 2050 and £98.4 billion (75.7 to 121.1) by 2154. For the transport sector the health benefits were £9.1 billion (7.0 to 11.2) by 2050 and £36.5 billion (28.1 to 44.9) by 2154. NZ building sector operating costs did not achieve break-even via efficiency savings, but with Greenhouse Gas (GHG) (lower benefits) break-even was achieved in 2052. With additional air pollution health benefits, building-sector time to break-even improved by between 3.1 (2.5 to 4.7) and 6.3 (4.7 to 7.6) years to between 2046 and 2049. Analysis found that removing gas cooking at home, for NZ, may result in greater concentration reductions than outdoor air pollution for NO2. Net Zero health and economic co-benefits are large, as are the changes needed, requiring political leadership and public engagement. Our findings are relevant to other countries facing the NZ transition.